Analysis of the Management of Hazardous and Toxic Waste (B3) in a dairy processing company - Sapta; Ahdha Aulia, Azrhi Nurfia Ahdha Aulia (Universitas Veteran Bangun Nusantara, 2024)
This article discusses the analysis of hazardous and toxic waste (B3) management in a dairy processing company. The research methods used include Literature Review, Field Study, and Interviews. The research findings reveal the types of waste generated, hazardous waste management permits (B3), temporary storage facilities for B3 waste, classification of stored B3 waste, B3 waste balance, B3 waste reporting, B3 waste treatment, emergency response readiness, and B3 waste management by third parties. The company has complied with all regulations related to B3 waste management, especially Minister of Environment and Forestry Regulation Number 6 of 2021 concerning Procedures and Requirements for Hazardous and Toxic Waste Management. This document provides in-depth insights into the B3 waste management process in the dairy processing company.